2016
DOI: 10.1016/j.bjan.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Associação de sufentanil a dose reduzida de bupivacaína hiperbárica em raquianestesia para cesariana: ensaio clínico randomizado

Abstract: A double blind randomized clinical trial of sufentanil as an adjunct in spinal anesthesia for cesarean section and, thereby, be able to reduce the dose of bupivacaine, a local anesthetic, with the same result of an anesthetic block with higher doses but with fewer perioperative side effects, such as hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…An earlier study suggested that adding sufentanil to intrathecal bupivacaine will reduce the required dose of local anesthetic in parturient. Nevertheless, they examined rather higher doses of bupivacaine ( 14 ). Another study reported that the maximum level of sensory block in caesarean patients who received bupivacaine 6 mg plus sufentanil 3.3 µg is comparable to those patients that received bupivacaine 12 mg without adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study suggested that adding sufentanil to intrathecal bupivacaine will reduce the required dose of local anesthetic in parturient. Nevertheless, they examined rather higher doses of bupivacaine ( 14 ). Another study reported that the maximum level of sensory block in caesarean patients who received bupivacaine 6 mg plus sufentanil 3.3 µg is comparable to those patients that received bupivacaine 12 mg without adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of sufentanil and bupivacaine in anesthesia of cesarean section prolongs the duration of analgesia and motor block. 12 – 15 Our study showed that there was no significant difference in the maximum sensory block time, motor block time, or hemodynamics between the two groups. These findings indicated that the combination of ropivacaine and sufentanil did not prolong the duration of anesthesia and had little effect on hemodynamics.…”
Section: Discussionmentioning
confidence: 68%